PENGAWASAN DINAS PERHUBUNGAN PROVINSI RIAU DALAM MENGATASI KENDARAAN YANG OVER DIMENSION OVER LOADING TAHUN 2021 - Febrianto, Eko; ', Isril (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
n this law, it is explained that road traffic and transportation have a strategic role in supporting national development and integration as part of efforts to advance general welfare as mandated by the 1945 Constitution of the Republic of Indonesia. Supervision according to Sastrohadiwirjo (2012) is a process in a series activities to ensure that a job can be carried out well with the plan that has been implemented and the stages that must be passed. This research was carried out at the Riau Province Transportation Service in the Road Traffic sector. The aim of this research is to determine the supervision of the Riau Province Transportation Service in dealing with vehicles that are Over Dimension Over Loading. The type of research used is descriptive qualitative. Qualitative research is a research method that directly describes phenomena that occur in the research object. The data obtained from this research is by interviews, observation and documentation. The research results show that it can be concluded that the implementation of Over Dimension Over Loading monitoring is already underway, but cannot be said to be optimal. The inhibiting factors in the implementation of Over Dimension Over Loading supervision by the Riau Provincial Transportation Service are the limited human resources involved directly in the field, the monitoring budget is insufficient, there are no goods transport rates so there are still many violations and the lack of good coordination between the Provincial Transportation Department Riau with the police and related agencies. Keywords: Supervision, Over Dimension, Over Loading